Mitsubishi Electric / Muhammad Hussein Syafiq Mohd Tholaat - Mohd Tholaat, Muhammad Hussein Syafiq (2022)
The company of my choice is Mitsubishi Electric and I have chosen the Jet Towel Smart Series as my product to run the analysis. The task that is given for this assignment is to identify the problem, pick out a solution upon the most critical problem, and pinpoint the best solution and recommendation of the product. In this case study, I have concluded the SWOT analysis where it is used to find out the strength, weaknesses, opportunities and threats of Jet Towel Smart Series. The problem that I identified from Jet Towel Smart Series is the recent scandal from product failure and lack of reputation, no monthly subscription or scaled payment, poor diversification and the product may cause serious health issues. The most critical problem that I found from this product is the health issues that are caused by the product and I came up with the best solution which is the improvement of the design by creating a space for hand sanitizer to be filled in.